G-protein coupled receptors and tau-different roles in alzheimer's disease - Chidambaram, Hariharakrishnan; Chinnathambi, Subashchandrabose (Neuroscience, 2020)
Post-translational modification of Tau, a microtubule-associated protein in the neuronal cell, plays a major role in Alzheimer's disease. Tau is an axonal protein expressed in mature neurons that promote the self-assembly of tubulin into microtubules and its stabilization in neurons. Phosphorylation of Tau makes it prone to aggregation at the intra-neuronal region leading to impaired neurotransmission and dementia. Tau aggregates undergo trans-cellular propagation by the release of fibrillar species into the extra-cellular environment from damaged and infected neurons that can be internalized by neighbouring neuronal and glia cells and promotes aggregation in healthy cells. G-protein coupled receptors, the largest group of seven transmembrane receptors, are involved in neuronal signal transduction in response to various signals such as hormones and neurotransmitters. In Alzheimer's disease, GPCRs are involved in phosphorylation of Tau through various downstream kinases such as GSK-3b, CDK-5 and ERKs signalling cascade. Several neuronal GPCRs that are involved in Tau phosphorylation are elaborated in this review. The astrocytic GPCR, Tau phosphorylation mediated by CaS receptors and its propagation by exosomes are also elaborated. In the microglia, the extra-cellular Tau binding to a chemokine GPCR, CX3CR1 triggers its internalization, whereas Tau phosphorylation at specific sites decreases its binding affinity to this receptor. Here we highlight the role of GPCRs in Tau phosphorylation and Tau interaction in different cells of the nervous system. Hence, the role of GPCRs are attaining more attention in the therapeutic field of Alzheimer's disease. Specific agonists/antagonists and allosteric modulators could be the potential target for therapy against GPCR-mediated Tau phosphorylation in Alzheimer's disease. (C) 2020 IBRO. Published by Elsevier Ltd. All rights reserved.
Keywords: Alzheimer's disease; GPCRs; microglia; Tau internalization; Tau phosphorylation; Tau propagation

Bacopa monnieri reduces Tau aggregation and Tau-mediated toxicity in cells - Dubey, Tushar; Kushwaha, Preeti; Thulasiram, H. V.; Chandrashekar, Madhura; Chinnathambi, Subashchandrabose (International Journal of Biological Macromolecules, 2023)
Alzheimer's disease is a neurodegenerative disease characterized by progressive memory loss and behavioral impairments. In the present study, the ethanolic extract of Bacopa monnieri was studied for its potency to inhibit Tau aggregation and rescuing of the viability of Tau-stressed cells. Bacopa monnieri was observed to inhibit the Tau aggregation in vitro. The cells exposed to Bacopa monnieri were also observed to have a low level of ROS and caspase-3 activity. The immunoblot and immunofluorescence analysis showed that Bacopa monnieri acts as an antioxidant and restored the Nrf2 levels in Neuro2a cells. Bacopa monnieri treatment to Neuro2a cells was observed to reduce the phospho-Tau load in formaldehyde-stressed cells. Furthermore, the treatment of Bacopa monnieri reduced the phosphorylation of GSK-3 beta in formaldehyde-stressed cells. Ran and NUP358 are the key proteins involved in nuclear transport. It was observed that formaldehyde treatment impaired the nuclear transport by missorting the NUP358 arrangement in Neuro2a cells. On the contrary, Bacopa monnieri treatment restored the NUP358 arrangement in cells. The overall results of the present study suggested that Bacopa monnieri could be considered a potent herb against Tau phosphorylation and Tau aggregation, which projects it as a promising formulation for Alzheimer's disease.
Keywords: Bacopa monnieri; GSK-3 beta; Nrf2; Nuclear transport; NUP358; Tau Aggregation; Tau phosphorylation